STRATEGI PROMOSI DALAM MENINGKATKAN PENJUALAN JAMU AL QOMAR (Studi Kasus Di Pondok Pesantren Sunan Kalijaga Pakuncen Patianrowo) - Cholifah, Binti Nur (Commodities, Journal of Economic and Business, 2021)
Sunan Kalijaga Islamic Boarding School is one of the huts in the Nganjuk area, which has economic independence and has many of the largest types of entrepreneurial activities, one of which is Al Qomar herbal medicine. Al Qomar herbal medicine has been sold on a national scale. Therefore researchers want to find out more about: 1) promotion strategy in increasing sales of Al Qomar herbal medicine. 2) contraints and solutions faced by Sunan Kalijaga islamic boarding school in promoting Al Qomar herbal products to increase sales. This types of research is field reserch using a descriptive analysis appoarch. In data collection researchers used interview methods and documentation. The researcher rechecked the data obtained and used the triangulation technique, with the aim of obtaining validity of the data. After that, analyze it and make conclusions. Based on the results of the study, the promotion strategy in increasing sales in Al Qomar Pakuncen Patianrowo Herbal Medicine is more emphasized in the promotion mix strategy, namely: 1) advertising (advertising) is to promote using radio media; 2) sales promotion (sales promotion), which is done by giving discounts when there are certain events, while also providing free samples of goods; 3) publicity and public relations, namely promotion by directly engaging the community in approaching the community with the aim of knowing the needs of the community for Al Qomar herbal products; 4) Indirect promotion, which is a sales methid that uses indiect marketing channels or media; 5) promotion of word of mouth (WOM) that is promotion carried out by consumers to prospective consumers who are of a recommending nature; 6) promotion through digital media that is promoting using facebook and google media; 7) promotion through networks or relationships that is establishing good connections with friends, relatives and even alumni in order to market products in a wider range.